SPIRITUAL UPGRADING OF STUDENTS IN MUSIC LESSONS - Khadichakhon Sharafutdinova; Najibullo ERGASHEV (Scholar Express Journal, 2024)
The educational process should develop not only the student's mind, but also his feelings, and should form moral skills and habits in him that are in accordance with the moral requirements of the society. To achieve this, the student's mind, emotions and will are affected. If any of these are neglected, it will be difficult to achieve the goal. The teacher leads the educational process, determines the students' activities, creates conditions for their participation in the social process.
Keywords: Musical heritage; educational; requirements